Investigation of sarcoidosis patients during COVID-19 pandemic - Kiani, Arda; Razavi, Fatemeh; Bandegani, Negar; Farahani, Mehradad; Abedini, Atefeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
No